PENGENALAN LITERASI MATEMATIKA PISA MELALUI KOMPETISI LITERASI MATEMATIKA BERBASIS ETNOMATEMATIKA PULAU-PULAU KECIL PERBATASAN - Sugiarto, Sigit; Lekitoo, John Nandito; Dahoklory, Andy Sunder Keer; Rupilele, Karolina; Koupun, Edeleta (Jurnal AbdiMas Nusa Mandiri, 2025)
The low mathematical literacy skills of junior high school students in Indonesia, especially those living in the Small Border Islands, require serious attention from various stakeholders. Improving students’ mathematical literacy is a shared responsibility that can begin with introducing the form of PISA mathematical literacy questions to junior high school students. One effort to achieve this is through an ethnomathematics-based mathematical literacy competition. This competition aims to provide knowledge and understanding of PISA mathematical literacy to students in the Small Border Islands, particularly on Moa Island. The activity was carried out as a form of community service by lecturers and students, consisting of four stages: initial observation, socialization, implementation, and evaluation. The participants of this competition were students from seven junior high schools on Moa Island, with a total of 57 participants. The increase in participants’ knowledge regarding PISA mathematical literacy question forms was measured using a questionnaire. The results showed an improvement in participants’ understanding before and after participating in the competition. However, test data also indicated that the mathematical literacy skills of students on Moa Island remain relatively low. Therefore, sustainable programs are needed to improve the mathematical literacy skills of students in the Small Border Islands, including Moa Island.